2019
DOI: 10.1186/s12935-019-0792-3
|View full text |Cite
|
Sign up to set email alerts
|

GSTM1 and GSTT1 null genotype increase the risk of hepatocellular carcinoma: evidence based on 46 studies

Abstract: Background It is well known that hepatocellular carcinoma (HCC) has been one of the most life-threatening diseases all over the world. Plenty of internal and extrinsic factors have been proven to be related to HCC, such as gene mutation, viral hepatitis, and Nitrosamines. Though previous studies demonstrated that glutathione S -transferase (GST) genotypes are associated with HCC, the conclusions are inconsistent. Therefore, we carried on a renewed meta-analysis to expoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Feng et al (32) have indicated that TGFB3 can function as a modulator to promote the metastatic phenotype of nonmetastatic HCC cells induced by TGFB1. GSTM1 polymorphisms have been identified as biomarkers of HCC development and risk in different regions (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Feng et al (32) have indicated that TGFB3 can function as a modulator to promote the metastatic phenotype of nonmetastatic HCC cells induced by TGFB1. GSTM1 polymorphisms have been identified as biomarkers of HCC development and risk in different regions (33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, including 46 studies, concluded that GSTT1 and GSTM1 null genotypes are associated with an increased risk of developing hepatocellular carcinoma (Li et al, 2019). Another study showed the association of GSTT1 null genotype with a greater risk of developing osteosarcoma (Moghimi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of two null alleles of the GSTM1 gene leads to the absence of the protein product of this gene, which contributes to the development of oxidative stress, causes an increase in the level of DNA adducts and can provoke the development of various liver pathologies. 11,12 A number of research findings show its important prognostic significance in the development of occupational diseases. 13,14 In contrast to these results, our study showed that there was no significant difference in the distribution of the GSTM1 gene genotypes among workers depending on the presence or absence of occupational pathology.…”
Section: Discussionmentioning
confidence: 99%